Shoulder complex and trunk coordination of individuals with severe hemiparesis following a constraint-induced movement therapy protocol: A case series - Pereira N.D. (2023)
© 2023 Elsevier LtdIntroduction: Constraint Induced Movement Therapy (CIMT) has been shown to be an effective rehabilitation technique in individuals with mild and moderate upper limb (UL) hemiparesis. The aim was to evaluate the effect the CIMT for improving paretic UL use and interjoint coordination with individuals in severe hemiparesis. Methods: Six individuals with severe chronic hemiparesis (mean age = 55 ± 16 years) received a UL CIMT intervention for 2 weeks. UL clinical assessments were conducted five times: two assessments at pre-intervention and then, one assessment at post-intervention and 1- and 3-month follow-up using the Graded Motor Activity Log GMAL) and the Graded Wolf Motor Function Test (GWMFT). Scapula, humerus and trunk coordination variability were assessed using the 3-D kinematics during arm elevation, combing hair, turning on the switch and grasp a washcloth. A paired t-test was used to check differences between coordination variability and a one-way ANOVA repeated measures was used to check differences between GMAL and GWMFT scores. Results: There were no differences in GMAL and GWMFT between the patient screening and the baseline data collection (p > 0.05). GMAL scores increased at post-intervention and at follow-ups (p < 0.02). GWMFT performance time score decreased at post-intervention and at 1-month follow-up (p < 0.04). Improvements in kinematic variability of the paretic UL at pre and post-intervention were observed in all tasks, except in the activity of turn on the light switch. Conclusion: Following the CIMT protocol, improvements in GMAL and GWMFT scores may reflect improvements in paretic UL performance, in real-life environment. Improvements in kinematic variability may reflect an improving of UL interjoint coordination for individuals with chronic severe hemiparesis.